Watching nanostructure growth: kinetically controlled diffusion and condensation of Xe in a surface metal organic network - Ahsan, Aisha; Gade, Lutz H. (Nanoscale, 2019)
Diffusion, nucleation and growth provide the fundamental access to control nanostructure growth. In this study, the temperature activated diffusion of Xe at and between different compartments of an on-surface metal organic coordination network on Cu(111) has been visualized in real space. Xe atoms adsorbed at lower energy sites become mobile with increased temperature and gradually populate energetically more favourable binding sites or remain in a delocalized ‘fluid’ form confined to diffusion along a topological subset of the on-surface network. These diffusion pathways can be studied individually under kinetic control via the chosen thermal energy kT of the sample and are determined by the network and sample architecture. The spatial distribution of Xe in its different modes of mobility and the time scales of the motion is revealed by Scanning Tunneling Microscopy (STM) at variable temperatures up to 40 K and subsequent cooling to 4 K. The system provides insight into the diffusion of a van der Waals gas on a complex structured surface and its nucleation and coarsening/growth into larger condensates at elevated temperature under thermodynamic conditions.